2014 Oceans - St. John's 2014
DOI: 10.1109/oceans.2014.7003138
|View full text |Cite
|
Sign up to set email alerts
|

TURTLE — Systems and technologies for deep ocean long term presence

Abstract: This paper describes the TURTLE project that aim to develop sub-systems with the capability of deep-sea long-term presence. Our motivation is to produce new robotic ascend and descend energy efficient technologies to be incorporated in robotic vehicles used by civil and military stakeholders for underwater operations. TURTLE contribute to the sustainable presence and operations in the sea bottom. Long term presence on sea bottom, increased awareness and operation capabilities in underwater sea and in particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In general, benthic landers, also known simply as landers, are any unmanned, unattached, autonomous, and instrumented underwater vehicle capable of gathering physical and chemical variables in situ over a given period. Their operational time can range from a few days, usually for biological studies, to several years, for physical oceanography studies (Ferreira et al 2014;Tengberg et al 1995). Deployment is usually performed in either one of two modes: (1) a free-fall mode, where control over the precise landing position is limited; or (2) a highprecision mode, commonly used to measure geomorphological features.…”
Section: Benthic Landersmentioning
confidence: 99%
“…In general, benthic landers, also known simply as landers, are any unmanned, unattached, autonomous, and instrumented underwater vehicle capable of gathering physical and chemical variables in situ over a given period. Their operational time can range from a few days, usually for biological studies, to several years, for physical oceanography studies (Ferreira et al 2014;Tengberg et al 1995). Deployment is usually performed in either one of two modes: (1) a free-fall mode, where control over the precise landing position is limited; or (2) a highprecision mode, commonly used to measure geomorphological features.…”
Section: Benthic Landersmentioning
confidence: 99%
“…Biswas et al [146] studied the influence incurred by climate change, specially the water-temperature change, on the fish catches in sustainable management of world fishery. Recently, Ferreira et al [147] reported the TURTLE project that explores the underwater subsystems. This study could reduce the operational expenditure, increase the capability of human activities, and benefit the sustainable operations in the sea bottom.…”
Section: B Environments Call For Sustainability 1) Urgent Actions To ...mentioning
confidence: 99%